2003
DOI: 10.1038/sj.jea.7500285
|View full text |Cite
|
Sign up to set email alerts
|

Use of stable isotopically labeled benzene to evaluate environmental exposures

Abstract: The use of stable, isotopically labeled compounds in controlled exposure experiments at environmentally relevant levels allows for the distinguishing of urinary metabolites associated with known exposure from background levels generally present in the urine. Exposures of volunteers to (13)C-benzene for 2 h at 40+/-10 p.p.b. were conducted after obtaining informed consent, and urinary phenol, catechol, hydroquinone and trans,trans- muconic acid were measured. Each isotopically labeled urinary metabolite was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 56 publications
1
59
0
Order By: Relevance
“…The natural abundance of each isotope can be predicted from the comparison of the height of the isotope peak with respect to the base peak. The values of the natural isotopic abundance of the common elements are obtained from several literatures [43][44][45][46] and presented in Table 1. Where, IAR Treated = isotopic abundance ratio in the treated sample and IAR Control = isotopic abundance ratio in the control sample.…”
Section: Methods Of Gc-ms Analysis and Calculation Of Isotopic Abundamentioning
confidence: 99%
See 2 more Smart Citations
“…The natural abundance of each isotope can be predicted from the comparison of the height of the isotope peak with respect to the base peak. The values of the natural isotopic abundance of the common elements are obtained from several literatures [43][44][45][46] and presented in Table 1. Where, IAR Treated = isotopic abundance ratio in the treated sample and IAR Control = isotopic abundance ratio in the control sample.…”
Section: Methods Of Gc-ms Analysis and Calculation Of Isotopic Abundamentioning
confidence: 99%
“…The gas chromatographymass spectrometry (GC-MS) can perform isotope ratio measurement at low micro molar concentration levels [43][44][45][46]. Recently, it has been reported that Mr. Trivedi's biofield energy treatment (The Trivedi Effect ® ) has the amazing capability to alter the physicochemical and thermal properties of nitrophenol such as crystallite size, particle size and thermal stability that might affect the rate of chemical reaction [24].…”
Section: Ortho-and Meta-nitrophenol (O-and M-nitrophenol)mentioning
confidence: 99%
See 1 more Smart Citation
“…These deviations from perfect chemical equivalence are termed as isotope effects. The isotopic abundance ratio is commonly reported in terms of atom percent and determined by high resolution mass spectrometry (HRMS spectrometry) [3]. For example, 13 C Atom percent 13 …”
Section: Introductionmentioning
confidence: 99%
“…Absolute abundances of isotopes are commonly reported in terms of atom percent. Various applications of isotope abundance study includes (a) the distribution of contaminant sources of any molecule on a native, regional, and global scale, (b) the identification and quantification of alteration reactions and (c) the characterization of elementary reaction mechanisms that govern product formation [11].…”
Section: Introductionmentioning
confidence: 99%